2015
DOI: 10.3390/molecules20045698
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Phenolic Compounds and Anthocyanins from Murta (Ugni molinae Turcz.) Fruits. Assessment of Antioxidant and Antibacterial Activity

Abstract: Berry fruit consumption has become important in the promotion of human health, mainly due to their phenolic compounds, which have been associated with protection against different pathologies, as well as antimicrobial and other biological activities. Consequently, there has been a growing interest in identifying natural antioxidants and antimicrobials from these plants. This study aimed to characterize the phenolic chemical composition and anthocyanin profile of murta (Ugni molinae Turcz.) fruit, and to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 48 publications
1
55
1
1
Order By: Relevance
“…In a first report, two anthocyanins (cyanidin-3-O-glucoside and peonidin-3-O-glucoside) were identified in murta whereas 18 anthocyanins (3-O-monoglycosylated and 3,5-O-diglycosylated delphinidins, cyanidins, petunidins, peonidins, and malvidins) were most abundant in calafate [28,37,38]. As can be expected by the wide variability of colors observed in murta ecotypes, subsequent studies [39] have described a greater number of anthocyanins where 3-O-glucosides of delphinidin, petunidin, and malvidin have been also identified in murta fruit. Based on these findings, murta ( Figure 4a) and calafate ( Figure 4b) could be used as promising sources of a wide variety of anthocyanins.…”
Section: Genotype Vs Environmentmentioning
confidence: 82%
See 2 more Smart Citations
“…In a first report, two anthocyanins (cyanidin-3-O-glucoside and peonidin-3-O-glucoside) were identified in murta whereas 18 anthocyanins (3-O-monoglycosylated and 3,5-O-diglycosylated delphinidins, cyanidins, petunidins, peonidins, and malvidins) were most abundant in calafate [28,37,38]. As can be expected by the wide variability of colors observed in murta ecotypes, subsequent studies [39] have described a greater number of anthocyanins where 3-O-glucosides of delphinidin, petunidin, and malvidin have been also identified in murta fruit. Based on these findings, murta ( Figure 4a) and calafate ( Figure 4b) could be used as promising sources of a wide variety of anthocyanins.…”
Section: Genotype Vs Environmentmentioning
confidence: 82%
“…The identification of other phenolic compounds in murta and calafate indicate the presence of phenolic acids (gallic acid, benzoic acid, p-coumaric acid, and hydrocaffeic acid), flavan-3-ols (epicatechin) and flavonols (quercetin, rutin, luteolin, kaempferol, and myricetin) in murta fruits [39,40]. On the other hand, 20 hydroxycinnamic acids and flavonols such as hyperoside, isoquercitrin, quercetin, rutin, myricetin, and isorhamnetin are more abundant in calafate fruits [39,41,42].…”
Section: Phenolic Acids and Other Flavonoids In Murta And Calafate Fruitmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Because NO is an important component of sinonasal innate immunity, 19,27,28 we hypothesized that anthocyanidins may activate sinonasal T2Rs to generate NO. In addition, anthocyanidin-rich plant extracts have antibacterial properties against Staphylococcus aureus, 29,30 Escherichia coli, 29,31 Corynebacterium diphtheria, 32 Moraxella catarrhalis, 32 Bacillus cereus, 33 and Pseudomonas aeruginosa. 34 However, other studies have indicated that anthocyanidins do not have antibacterial effects against B. cereus, 34 E. coli, 34,35 or P. aeruginosa, 30 or that anthocyanidins only reduce inflammation.…”
mentioning
confidence: 99%
“…fruit, which is a Chilean berry, exhibit antioxidant activity via phenolic compounds (Alfaro et al, 2013;Augusto et al, 2014;Suwalsky and Avello, 2014;Rodríguez et al, 2014;Junqueira-Gonçalves et al, 2015;Jofré et al, 2016). For being a seasonal fruit, the drying process is considered an adequate technique for its preservation which saves the antioxidant properties provided by its polyphenolic components (Alfaro et al, 2014).…”
Section: Introductionmentioning
confidence: 99%